Detection of Aspergillus-specific antibodies by agar gel double immunodiffusion and IgG ELISA in feline upper respiratory tract aspergillosis. Issue 3 (March 2015) - Barrs, V.R.; Ujvari, B.; Dhand, N.K.; Peters, I.R.; Talbot, J.; Johnson, L.R.; Billen, F.; Martin, P.; Beatty, J.A.; Belov, K.
Highlights Feline antibodies against cryptic Aspergillus spp. cross react with an aspergillin containing A. fumigatus antigens. Brachycephalic cats are prone to upper respiratory tract aspergillosis (URTA). The agar gel immunodiffusion (AGID) assay has low sensitivity for diagnosis of URTA. IgG ELISA has high sensitivity and specificity for diagnosis of URTA. This study provides evidence that cats with URTA are systemically immunocompetent.